New Evidence on the Urbanization of Global Poverty - Ravallion, Martin; Chen, Shaohua; Sangraula, Prem (World Bank, Washington, DC, 2012)
The authors provide new evidence on the extent to which absolute poverty has urbanized in the developing world, and the role that population urbanization has played in overall poverty reduction. They find that one-quarter of the world's consumption poor live in urban areas and that the proportion has been rising over time. By fostering economic growth, urbanization helped reduce absolute poverty in the aggregate but did little for urban poverty. Over 1993-2002, the count of the "$1 a day" poor fell by 150 million in rural areas but rose by 50 million in urban areas. The poor have been urbanizing even more rapidly than the population as a whole. Looking forward, the recent pace of urbanization and current forecasts for urban population growth imply that a majority of the poor will still live in rural areas for many decades to come. There are marked regional differences: Latin America has the most urbanized poverty problem, East Asia has the least; there has been a "ruralization" of poverty in Eastern Europe and Central Asia; in marked contrast to other regions, Africa's urbanization process has not been associated with falling overall poverty.